Pharmacokinetics, pharmacodynamics, and safety of peginterferon beta‐1a in subjects with normal or impaired renal function. (23rd September 2014) - Hu, Xiao; Seddighzadeh, Ali; Stecher, Scott; Zhu, Ying; Goyal, Jaya; Matson, Mark; Marbury, Thomas; Smith, William; Nestorov, Ivan; Hung, Serena
Abstract Peginterferon beta‐1a was efficacious in a Phase 3 relapsing multiple sclerosis trial, and its safety profile was consistent with other beta interferons. This study evaluated the impact of renal impairment on the pharmacokinetics and pharmacodynamics (neopterin elevation; a biomarker of pharmacological activity induced by interferon beta‐1a) of peginterferon beta‐1a following a single subcutaneous dose at 63 μg (n = 5) or 125 μg (n = 30). The results showed a fractional increase in area‐under‐the‐concentration‐time curve (AUC [30–53%]) and peak serum concentration (Cmax [26–42%]) in subjects with mild, moderate, and severe renal impairment, versus healthy subjects; AUC and Cmax were similar for healthy subjects and end‐stage‐renal‐disease patients receiving hemodialysis. Pharmacokinetic simulation showed that the steady state concentration overlapped in the majority of healthy subjects and subjects with severe renal impairment. Neopterin baseline, peak concentration, and AUC increased as renal function decreased. Peginterferon beta‐1a was well tolerated in all groups. These results do not warrant peginterferon beta‐1a dose adjustment in subjects with renal impairment.